Factor Stress Keluarga pada Remaja SMK di Salah Satu Sekolah Negeri di Yogyakarta - Nurmaulia Khotmi (LPPM Politeknik Pratama, 2023)
Stress can be experienced by anyone regardless of age. In this study the stress that occurs in adolescents is caused by problems that exist in the family. This study aims to determine the factors that cause family stress in adolescents. In this study the data collection method is through screening and interviews. Screening was carried out using the student health screening module from the Ministry of Health 2006. After that, interviews were carried out on each youth, and using SUD (subjective unite discomfort) to see the level of stress experienced related to problems with the family. The results of this study are the stress experienced by adolescents, including the attitudes of both parents who are felt to be unfair to their children in terms of attention, needs and attitudes. In addition, parents are considered to always compare their children with their siblings, parents who do not appreciate their children's achievements or work results, parents who are not harmonious, parents do not care about their children, and parents do not care consistently.